The Effect of Job Demands on Burnout with Work-Life Balance as A Mediation Variable in Nurses at Lubuk Basung Regional General Hospital: JEL Classification: J28, J81, M54, M12, I12 - Nahya Nofika; Chichi Andriani (Journal of Management and Administration Provision, 2026)
Hospitals are required to effectively manage their nursing workforce to maintain the quality and sustainability of healthcare services. One of the major challenges faced by nurses is Burnout resulting from high Job Demands. This study aims to analyze the effect of Job Demands on Burnout with Work-Life Balance as a mediating variable among inpatient nurses at Lubuk Basung Regional General Hospital. This research uses a quantitative approach with a descriptive causal design. Data were collected through questionnaires distributed to 109 inpatient nurses at Lubuk Basung Regional General Hospital using a total sampling (census) technique. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results show that Job Demands has a positive and significant effect on Burnout. Job Demands also has a negative and significant effect on Work-Life Balance, and Work-Life Balance has a negative and significant effect on Burnout. Furthermore, Work-Life Balance is proven to partially mediate the effect of Job Demands on Burnout. These findings indicate that higher job demands experienced by nurses reduce their ability to maintain work-life balance, which in turn increases the risk of Burnout.